Ergo-aesthetic concept design approach among bamboo furniture manufacturers in Malaysia - Abdul Hamid, Abdul Ghafur; Abd Rahman, Khairul Aidil Azlin; Zainal Abdullah, Muhammad Ezran (IAEME Publication, 2020)
In general, the concept of ergo-aesthetic discloses the equilibrium of human behavioural character with form, shape, and symbolism incorporated into furniture design. This harmony synthesis is achieved throughout responses of behaviour and senses inside the design process. Many new developments have been made in the industry, especially on understanding the advantages and potentials of bamboo characters; however, these developments are not specific to designing with an aesthetic value in bamboo furniture design. Thus, this study focuses on the ergo- aesthetic principles incorporated in the design process to achieve a better output of bamboo furniture design among bamboo manufacturers in Malaysia. As such, ergonomic and aesthetic are the fundamental components that need to be considered throughout the design process as the implementation of ergo-aesthetic principles into a bamboo furniture design process through behaviour and cultural perspectives may lead to the enhancement of the quality of bamboo furniture output.